Exploratorium cookbook III : a construction manual for Exploratorium exhibits - Hipschman, Ron (Exploratorium, 1987)
Directions for creating science exhibits which demonstrate scientific principles in such areas as mechanics, electricity, stereoscopic vision, sound, heat, and light.